Numerical study of sandwich panel with a new bi-directional Load-Self-Cancelling (LSC) core under blast loading - Li, Z.; Chen, Wensu; Hao, Hong (2018)
© 2018 A new form of bi-directional Load-Self-Cancelling (LSC) sandwich panel is proposed in this paper. An array of square dome shaped steel sheet as core of the proposed sandwich panel is designed to cancel a certain amount of load during blast event owing to its arching geometry. The blast resistance and energy absorption capabilities of the sandwich panel are investigated numerically by using finite element analysis software LS-DYNA. The peak deflection of centre point on back face sheet, internal energy and peak boundary reaction forces are compared among monolithic plate, multi-arch uni-directional LSC structure, sphere dome structure and the proposed bi-directional LSC square dome sandwich panel. It is found that using the proposed bi-directional LSC square dome leads to 69%, 48% and 56% reduction in the out-of-plane boundary reaction force as compared to the flat plate, multi-arch panel and grid sphere panel, respectively. In addition, parametric studies of the influences of dome number, height, and layer material on the performances of the proposed bi-directional LSC sandwich panel subjected blast loads of different intensities are carried out to investigate the panel configuration on the effectiveness of its blast resistance and load-self-cancelling capability. The results demonstrate the superiority of the sandwich panel with the proposed bi-directional LSC core.